Second-harmonic generation circular dichroism studies of osteogenesis imperfecta - Chen, Xiyi (Opt Lett, 2012)
We report the use of second-harmonic generation (SHG) microscopy in conjunction with circular dichroism (CD) to differentiate normal skin from that in the connective tissue disorder osteogenesis imperfecta (OI). Osteogenesis imperfecta results from mutations in the collagen triple helix, where the individual chains are defective, leading to abnormal folding, and ultimately, abnormal fibril/fiber organization. Second-harmonic-generation circular dichroism successfully differentiated normal human and OI skin tissues, whereas other SHG polarization schemes did not provide discrimination, suggesting this approach has high sensitivity for studying the difference in chirality in the mutated collagen. We further suggest that the method has clinical diagnostic value, as it could be performed with minimal invasion.